Changes of gut microbiota under different nutritional methods in elderly patients with severe COVID-19 and their relationship with prognosis - Zhang, Jiawei; Deng, Jiaxin; Li, Juan; Su, Yuping; Hu, Jiancong; Lin, Dezheng; Su, Mingli; Chen, Yongcheng; Liao, Sen; Bai, Xuhao; Lv, Miwei; Xu, Tian; et al. (Frontiers in Immunology, 2023)
The clinical progression of individuals afflicted with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection exhibits significant heterogeneity, particularly affecting the elderly population to a greater extent.Consequently, the association between nutrition and microbiota has garnered considerable interest. Hence, the objective of this study was to gather clinical data pertaining to the influence of diverse nutritional support interventions on the prognosis of geriatric patients with COVID-19, while additionally examining the fecal microbiota of these individuals to assess the repercussions of microecological alterations on their prognostic outcomes.Results: A total of 71 elderly patients diagnosed with severe COVID-19 were included in this study. These patients were subsequently divided into two groups, namely the enteral nutrition (EN) group and the parenteral nutrition (PN) group, based on the type of nutritional support therapy they received after admission. The occurrence of complications was observed in 10.4% of patients in the EN group, whereas it was significantly higher at 69.6% in the PN group (P<0.001). Furthermore, the 60-day mortality rate was 2.1% (1/48) in the EN group, while it was notably higher at 30.4% (7/23) in the PN group (P=0.001). To identify the independent predictors of 60-day mortality, stepwise logistic regression analysis was employed.Among different bacterial groups, Enterococcus_faecium (18.19%) and Pseudomonas_aeruginosa (1.91%) had higher average relative abundance in the PN group (P<0.05). However, the relative abundance of Ruminococcus was higher in the EN group. Further Spearman correlation analysis showed that Enterococcus_faecium was positively correlated with poor clinical prognosis, while Ruminococcus was negatively correlated with poor clinical prognosis.: This study shows that the changes in the composition of intestinal flora in elderly COVID-19 patients receiving different nutritional support strategies may be related to different clinical outcomes. The abundance of Enterococcus_faecium in elderly COVID-19 patients receiving PN is significantly increased and is closely related to poor clinical outcomes. It highlights the potential of microbiome-centric interventions to mitigate and manage COVID-19 in older adults with different nutritional support options.